Evaluation of the role of clathrin and bacterial viability in the endocytosis of Lawsonia intracellularis - Pereira, Carlos Eduardo Real; Resende, Talita Pilar; Daniel, Amanda Gabrielle de Souza; Vannucci, Fabio Augusto; Gebhart, Connie; Guedes, Roberto Mauricio Carvalho (Frontiers in Veterinary Science, 2023)
Lawsonia intracellularis is an obligate intracellular bacterium and causative agent of proliferative enteropathy. The pathogenesis of L. intracellularis is not completely understood, including the endocytic mechanisms to access the host cell cytoplasm. In this study, we evaluated the mechanisms involved in endocytosis of L. intracellularis in vitro using intestinal porcine epithelial cells (IPEC-J2). Confocal microscopy was used to co-localize L. intracellularis and clathrin. Clathrin gene knockdown was then applied to verify whether L. intracellularis endocytosis is clathrin-dependent. Finally, internalization of viable and nonviable (bacteria were inactivated by heat) L. intracellularis organisms were assessed to study the role of the host cell during bacterial endocytosis. L. intracellularis organisms were observed co-localized with clathrin by confocal microscopy but the amount of L. intracellularis internalized in cells, with and without clathrin knockdown, did not differ statistically. The internalization of nonviable L. intracellularis showed a decrease in the internalization in cells with less clathrin synthesis (P<0.05). The present study is the first to elucidate the incolvement of clathrin in the endocytosis of L. intracellularis. Clathrin-mediated endocytosis was shown to be an important, but not required, process for L. intracellularis internalization in porcine epithelial cells. Independence of bacterial viability for host cell internalization was also confirmed.